Regulation of capacitative and non-capacitative Ca2+ entry in A7r5 vascular smooth muscle cells - TAYLOR,COLIN W (Sociedad de Biología de Chile, 2004)
A capacitative Ca2+ entry (CCE) pathway, activated by depletion of intracellular Ca2+ stores, is thought to mediate much of the Ca2+ entry evoked by receptors that stimulate phospholipase C (PLC). However, in A7r5 vascular smooth muscle cells, vasopressin, which stimulates PLC, empties intracellular Ca2+ stores but simultaneously inhibits their ability to activate CCE. The diacylglycerol produced with the IP3 that empties the stores is metabolized to arachidonic and this leads to activation of nitric oxide (NO) synthase, production of NO and cyclic GMP, and consequent activation of protein kinase G. The latter inhibits CCE. In parallel, NO directly activates a non-capacitative Ca2+ entry (NCCE) pathway, which is entirely responsible for the Ca2+ entry that occurs in the presence of vasopressin. This reciprocal regulation of two Ca2+ entry pathways ensures that there is sequential activation of first NCCE in the presence of vasopressin, and then a transient activation of CCE when vasopressin is removed. We suggest that the two routes for Ca2+ entry may selectively direct Ca2+ to processes that mediate activation and then recovery of the cell.